2011
DOI: 10.1158/0008-5472.can-10-2289
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen, Flaxseed, and the Lignan Enterolactone Increase Stroma- and Cancer Cell–Derived IL-1Ra and Decrease Tumor Angiogenesis in Estrogen-Dependent Breast Cancer

Abstract: The proinflammatory cytokines IL-1a and IL-1b promote tumor angiogenesis that might be counteracted by the IL-1 receptor antagonist (IL-1Ra), anakinra, a clinically approved agent. A diet with high amounts of phytoestrogens, such as flaxseed (Flax), genistein (GEN), and the mammalian lignan enterolactone (ENL), may affect breast cancer progression in a similar fashion as the antiestrogen tamoxifen. Both cancer cells and tumor stroma may be targets for cancer therapy. By using microdialysis in a model of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 42 publications
3
59
0
1
Order By: Relevance
“…We have previously found an association of estrogen levels and the in vivo levels of several inflammatory biomarkers in human breast tissue. 4,5,7,9,11,34 In these studies, both pre-and post-menopausal women and patients investigated before and after anti-estrogen treatment were included, thus reflecting cohorts of women with a wide range of hormone levels, whereas in the present study, postmenopausal women exhibiting minor variation of estradiol levels were included. Hence, correlations with estrogen may not be expected in this selected population.…”
Section: E1229723-4mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found an association of estrogen levels and the in vivo levels of several inflammatory biomarkers in human breast tissue. 4,5,7,9,11,34 In these studies, both pre-and post-menopausal women and patients investigated before and after anti-estrogen treatment were included, thus reflecting cohorts of women with a wide range of hormone levels, whereas in the present study, postmenopausal women exhibiting minor variation of estradiol levels were included. Hence, correlations with estrogen may not be expected in this selected population.…”
Section: E1229723-4mentioning
confidence: 99%
“…We have previously shown increased extracellular in vivo levels of several inflammatory mediators, such as interleukin (IL)-1, IL-8, chemokine (C-C motif) ligand (CCL) 2, CCL5, leptin, and vascular endothelial growth factor (VEGF) in breast cancers of women and an association with sex steroids of these factors in normal human breast tissue. [4][5][6][7][8][9][10][11][12] Mammographic density has been associated with increased risk of breast cancer. 13 In a meta-analysis women with >75% dense breast area have a 4-fold increased risk of developing breast cancer compared to women with <5% dense breast area.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of immune cells express the ER, and estrogen affects the expression of inflammatory mediators in neutrophils and macrophages (8,9). We have shown that estrogen increases the influx of macrophages into breast cancers and induces a protumorigenic phenotype (M2) in these cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Our group previously reported the release of IL-1s from both cancer and stromal cells in a xenograft nude mouse model, and an alteration of IL-1 levels after tamoxifen or diet modification by flaxseed and lignan enterolactone, but not by genistein (237). In Paper I of this thesis, we therefore intended first to determine the presence of IL-1 cytokines in the extracellular space of human breast tissue in vivo, and to investigate the role of sex steroids in the regulation of IL-1 cytokines in normal human breast tissue.…”
Section: Resultsmentioning
confidence: 95%